Dormancy, germination and seed bank storage: a study in support of ex situ conservation of macrophytes of southwest Australian temporary pools - Tuckett, R.E.; Merritt, D.J.; Hay, F.R.; Hopper, S.D.; Dixon, K.W. (Wiley, 2010)
1. Vernal pools and rock pools (gnammas) in the Southwest Australian Floristic Region are forms of temporary wetlands that are under threat. Some of their aquatic macrophytes are rare and/or endemic, and there is a need to develop off‐site seed banks to assure their conservation. Here, we report results of the first comprehensive study of the seed germination, dormancy and seed storage behaviour of nine indigenous macrophyte species.2. Seeds of Glossostigma drummondii, Myriophyllum balladoniense, M. lapidicola, M. petreaum and Triglochin linearis were non‐dormant, whereas those of Damasonium minus, Glossostigma sp. (currently undescribed), G. trichodes and Myriophyllum crispatum were dormant. Non‐dormant seeds germinated over a range of temperatures (5–20 °C) but temperatures at which highest germination occurred were species specific. All species demonstrated a germination preference for the light. Warm stratification substantially increased germination of dormant Glossostigma trichodes seeds and all dormancy‐breaking treatments partially overcame dormancy in Glossostigma spp.3. Seeds possessed orthodox storage behaviour (tolerating drying to 5% moisture content and storage at −18 °C) and are thus amenable to seed banking as a means of ex situ conservation.4. It appears that seeds of most species are able to germinate upon inundation as long as they are situated at the soil surface. Thus, species are opportunistic and respond to the first rains of the season providing prompt ecological cuing in an environment vulnerable to rapid drying events. Maintaining the integrity of the soil crust may be an important first step for on‐site conservation if seeds are in the superficial layers.